The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.21577/0100-4042.20170374
|View full text |Cite
|
Sign up to set email alerts
|

Cuprous Oxide Nanoparticles: Preparation and Evaluation of Antifouling Activity

Abstract: There are few methods to obtain uniform and well dispersed cuprous oxide nanoparticles, which limits its application widely. In this research, an improved method to prepare nanoparticles was introduced. Cuprous oxides were prepared by the reduction of cupric nitrate, with hydrazine hydrate as a reductant in the presence of glucose. The nanoparticles formed have the characteristics of small particle size and uniform distribution. The crystalline structure and morphological characteristics were analyzed by XRD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…By using the Debye-Scherrer equation, the average crystalline size of CuO NPs is 22 nm. The findings were intimately associated with the results for nanoparticles of cuprous oxide (Shi et al, 2019).…”
Section: Xrd Analysissupporting
confidence: 74%
“…By using the Debye-Scherrer equation, the average crystalline size of CuO NPs is 22 nm. The findings were intimately associated with the results for nanoparticles of cuprous oxide (Shi et al, 2019).…”
Section: Xrd Analysissupporting
confidence: 74%
“…However, to this end, only few precious metals such as silver and gold are recovered from the PCBs, whereas most of the base metals being of lesser economical values are left as such which eventually ends up in landfills. , One such metal is Cu, which also happens to be in major proportion as compared to other metals in PCBs. Recently, a lot of efforts have been advocated to trap this metal and put back in recycling loop, and therefore many laboratories have reported processes related to its recovery. Cu, apart from having applications in the electronic industry as a conductive metal, have recently shown huge potential in various futuristic technologies if produced in the form of nanoparticles (NPs) . Copper oxide nanoparticles, commonly referred to as CuO NPs, have shown quite unique physicochemical properties, e.g., electron correlation effects and spin dynamics, narrow band gaps, extremely high surface areas, and unusual crystal morphologies, and therefore have found immense application in various advance fields, like catalysts in rocket propellants, antifouling material in ship hulls and submarines, semiconductive materials in the electronic industry, electrode materials for batteries, catalysis, sensors, antiviral and antibacterial materials for public safety, especially during pandemics, etc. Therefore, there exists huge potential in selectively recovering Cu from e-waste and its transformation to CuO NPs for high-end applications.…”
Section: Introductionmentioning
confidence: 99%
“…11−15 Cu, apart from having applications in the electronic industry as a conductive metal, have recently shown huge potential in various futuristic technologies if produced in the form of nanoparticles (NPs). 16 Copper oxide nanoparticles, commonly referred to as CuO NPs, have shown quite unique physicochemical properties, e.g., electron correlation effects and spin dynamics, narrow band gaps, extremely high surface areas, and unusual crystal morphologies, and therefore have found immense application in various advance fields, like catalysts in rocket propellants, 17 antifouling material in ship hulls and submarines, 18 semiconductive materials in the electronic industry, 19 electrode materials for batteries, 20 catalysis, 21 sensors, 22 antiviral and antibacterial materials 23 for public safety, especially during pandemics, etc. Therefore, there exists huge potential in selectively recovering Cu from e-waste and its transformation to CuO NPs for highend applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many types of nanoparticles and their derivatives, including metal and metal oxide nanoparticles such as silver (Ag), silver oxide (Ag 2 O), titanium dioxide (TiO 2 ), silicon (Si), copper oxide (CuO), zinc oxide (ZnO), gold (Au), calcium oxide (CaO), and magnesium oxide (MgO), illustrate the important role for antimicrobial activity . Among several metal and metal oxide nanoparticles, copper-based nanoparticles have been receiving particular attention to employ as antimicrobial materials (registered at the U.S. Environmental Protection Agency (EPA) in 2008) due to low costs of the material source and a wide spectrum of antimicrobial activity against different species of microbes. Noticeably, copper­(I) oxide or cuprous oxide (Cu 2 O) as one of copper oxide forms has attracted considerable interest due to its outstanding properties such as its low energy band gap (2.18 eV), photocatalytic and catalytic power, and broad spectrum of antibacterial activity. Several previous works reported that Cu 2 O compounds provided better antiviral efficacy over cupric oxide (CuO). They have been demonstrated to effectively inhibit influenza, hepatitis C virus (HCV), herpes simplex virus (HSV), feline calicivirus (FCV), and bacteriophages on solid-state surfaces and in solution. Recently, Cu 2 O has attracted much attention from many scientists because it can be employed in smart antiviral materials against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).…”
Section: Introductionmentioning
confidence: 99%